Cultural Islamic Education Form the Character of Multicultural Elementary School Students - Baharuddin Baharuddin; St. Warda Hanafie Das; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2024)
This study aims to analyze how cultural Islamic education can shape the character of elementary school students in a multicultural environment. Cultural Islamic education focuses on the application of Islamic values within the context of diverse cultures, emphasizing tolerance, mutual respect, and understanding of differences. This research uses a qualitative approach with a case study method in several elementary schools that implement cultural Islamic education in a multicultural setting. Data were collected through in-depth interviews with teachers, students, and parents, as well as observations of teaching and learning activities in the classroom. The results of the study show that cultural Islamic education has a positive impact on shaping the students' character, particularly in the development of tolerance, empathy, and openness to cultural diversity. Furthermore, cultural Islamic education also helps students to better understand and appreciate cultural and religious differences in their environment, which in turn supports the creation of harmonious social relationships within the multicultural school community. This study recommends strengthening the integration of Islamic values into the elementary education curriculum as an effort to shape a more inclusive and multicultural student character